El tejido del cosmos. Tiempo, espacio y arte de la hamaca entre los ette (chimila) - Juan Camilo Niño Vargas (Journal de la Société des Américanistes)
The aim of this article is to put forward a model of the Ette universe, a Chibchan speaking people of northern Colombia, through an analysis of the relationship between cosmological principles and material culture. The way in which time and space are experienced at a cosmological level is compared with conceptions of the hammock and the way it is used. We show how this object materializes a complex set of cosmic notions: from the concave, bipolar and instable shape of the earth, to the tripartition between a human present located in the middle, an animal past placed below and, finally, a divine future situated above.